Clinical and imagenological evaluation of the temporomandibular joint in patients undergoing condylectomy for the treatment of unilateral hyperplasia. Case series study - Laguna-Monagas, Héctor Andrés (2021)
Unilateral condylar hyperplasia is a non-neoplastic and self-limiting overgrowth of the mandibular condyle that usually begins during puberty, predominates in women and is considered an aberration of the normal growth mechanism of the condyle. This abnormal growth continues until the mid-20s and produces mandibular prognostism, facial and occlusal asymmetry with progressive displacement of the mandible to the contralateral side. The purpose of this report was to describe the cases of two female patients (23 and 25 years old) with unilateral condylar hyperplasia treated with high condylectomy and orthognathic surgery, with emphasis on clinical and imaging aspects and late post-surgical follow-up. Both patients presented satisfactory cosmetic results, without pain / noise related to the temporomandibular joint, mouth opening within the normal range, and class I canine and molar relationship. Computed tomography showed signs of remodeling in the affected condyle. High condylectomy combined with orthognathic surgery is an adequate treatment in cases of unilateral hyperplasia, restoring functionality and aesthetics to the patient. The bone remodeling observed in the intervened condyles seems to indicate that the condylar head maintains its adaptive capacity even in adult patients.